Korioamnionitis Sebagai Faktor Risiko Terjadinya Persalinan Preterm - Rahmi, Elita; Respati, Supriyadi Hari; Melinawati, Eriana (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Premature Rupture of Membranes (PROM) is one causes of fetal mortality and morbidity. Suspected chorioamnionitis is a major cause of preterm labor. Methods: This study was observational analytic cross-sectional approach. Sample of 694 study subjects that satisfy with inclusion and exclusion criteria were taken from the medical records of patients who gave birth in RSUD Dr. Moewardi. The data was analyzed using bivariate analysis and processed with Statistical Product and Service Solutions (SPSS) for Windows 20:00. Results: Chorioamnionitis is a risk factor 1.045 times to preterm delivery occur (OR = 1045; CI = 95%, 0737, 1483, p = 0804). Chorioamnionitis causedÂ death of neonatal mortality 1.554 times compared with norma pregnancy (OR = 1554; CI = 95%, 0790, 3057, p = 0.194). Chorioamnionitis 1.747 times risk factors for occur asphyxia in preterm labor and statistically significant (OR = 1747; CI = 95%, 1114, 2741, p = 0.014). Conclusions: There was no significant relationship between chorioamnionitis with preterm labor and chorioamnionitis with neonatal mortality. There is a significant relationship between chorioamnionitis with asphyxia. Keywords: PROM, Chorioamnionitis, preterm labor